An Empirical Performance Evaluation of Open-end Funds in China - ZHOU, Weiwei (2007)
A variety of academic researches have been carried out to evaluate the performance of mutual funds. These findings and results may differ in different period. The aim of this research is to evaluate the performance of 20 open-end stock funds for the period of 6 years from August 2004 to July 2007. The data of the fund is collected on monthly basis. Funds are evaluated using the risk-adjusted measures and market timing ability measure. It is concluded that the neither the open-end funds in China outperform the market nor the portfolio managers present the market timing ability.